Accessing medical care in the era of the digital revolution: arguing the case for the “digitally marginalised” - Choolayil, Anoop C.; Paranthaman, Sadhishkumar; Kuttiatt, Vijesh Sreedhar (Frontiers in Digital Health, 2024)
This article explores the intersection of healthcare accessibility and digitalisation from a rights perspective. Drawing from two illustrative cases presented to a filariasis management clinic in Puducherry, where the authors are affiliated, the article argues that despite the multiple benefits that digital health poses, there are individuals and sections of society that experience marginalisation in healthcare owing to digitalisation. Collating the data generated through the observations of the authors and the narratives of the patients, the article illustrates that such marginalisation can originate even from a relatively simple ICT adaptation like text message-based appointments, inducing health inequities. The impact of such digital marginalisation disproportionately affects vulnerable sections like older adults and the rural population in an intersectional pattern where disadvantages compound to produce larger health inequities for the affected. The study advocates for bridging the digital divide through efforts including digital literacy–when possible–and alternative solutions like dedicated helpdesks, training healthcare staff and involving NGOs and voluntary organisations to ensure health equity for the digitally marginalised.